Synthesis and textural characterization of a templated nanoporous carbon from MCM-22 zeolite and its use as adsorbent of amoxicillin and ethinylestradiol - Barrera, Deicy (2014)
A templated nanoporous carbon was obtained from a zeolite MCM-22 type. The study about their textural properties was carried out by means of adsorption isotherms of nitrogen and carbon dioxide at 77 and 273 K, respectively. Due to the importance of the microporosity of these materials to be used as adsorbents, the micropore volume was analyzed by different methods/models (Dubinin–Radushkevich, αs-plot and Density Functional Density). The templated carbon obtained was evaluated in the adsorption of amoxicillin and ethinylestradiol from aqueous solutions. A relationship between the textural properties and the adsorption capacities of amoxicillin and ethinylestradiol on the templated carbon was analyzed. Results were compared with the adsorption capacities of other carbon materials as a commercial activated carbon and a templated carbon CMK-3 type.